The Guatemala Community Daycare Programme: effective food aid targeting in urban areas - Ruel, Marie T. (International Food Policy Research Institute, 2003)
The programme has a substantial positive impact on the diet of children. It also complements the basic livelihood strategies of poor urban women working outside the home.; Urban Challenges to Food and Nutrition Security